Get Out the Vote : How to Increase Voter Turnout - Green, Donald P., 1961-; Gerber, Alan S. (Book collections on Project MUSE., 2008)
"Expanded and updated edition incorporates data from more than 100 new studies, shedding light on the cost-effectiveness and efficiency of various campaign tactics, including door-to-door canvassing, e-mail, direct mail, and telephone calls. Two new chapters focus on the effectiveness of mass media campaigns and candidate forums and Election Day festivals"--Provided by publisher